2019
DOI: 10.1007/s12116-019-09295-0
|View full text |Cite
|
Sign up to set email alerts
|

Parties, Civil Society, and the Deterrence of Democratic Defection

Abstract: The third wave of democratization has given way to a reverse wave of autocratization. A critical question is what can be done to prevent democratic breakdowns and make democracy endure. A large body of historical-narrative and small-N comparative scholarship has suggested that an active mobilized civil society and institutionalized political parties can be mobilized to protect democracy from authoritarian takeovers. We provide the first rigorous set of empirical analyses to test this argument using data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 90 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Previous studies have shown how populism in power erodes horizontal accountability in Latin America (Ruth, 2018), and that diagonal accountability can prevent democratic erosion (Bernhard, 2020;Bernhard et al, 2015Bernhard et al, , 2020. The main findings of this article are that technocratic populism has illiberal tendencies expressed best in its efforts at executive aggrandizement (cf.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previous studies have shown how populism in power erodes horizontal accountability in Latin America (Ruth, 2018), and that diagonal accountability can prevent democratic erosion (Bernhard, 2020;Bernhard et al, 2015Bernhard et al, , 2020. The main findings of this article are that technocratic populism has illiberal tendencies expressed best in its efforts at executive aggrandizement (cf.…”
Section: Discussionmentioning
confidence: 74%
“…Public protest rejected the new social contract of passivity and demanded accountability (cf. Bernhard, 2020;Bernhard et al, 2015Bernhard et al, , 2020. Nevertheless, ANO remains the strongest party (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is good reason to doubt that strong associational development is correlated in any way with democratic failure (Bernhard et al 2020;Cornell et al 2016), both Berman and Riley do point out that civil society actors can play an important role in the complex of conditions that can promote democratic regress (whether that is breakdown or backsliding). Substantively, Bermeo (2003) strongly counters this argument placing the blame for the polarisation of civil society on the encouragement of elites, and presents evidence for this from not only the usual suspects of interwar Western Europe and postwar South America, but also interwar East-Central Europe as well.…”
Section: Civil Society and The Problem Of Democratic Backslidingmentioning
confidence: 99%